Study of combining ability for yield and yield attributing traits in Brassica rapa ssp. Brown Sarson (Journal of Oilseed Brassica, 2026)
The present investigation on Brassica rapa ssp. Brown Sarson genotypes is an attempt to study variations and to generate variability through hybridization and also to obtain genetic information on some yield attributes for selection in segregating generations. Seven promising parents viz. KBS-33, KBS-38, KBS-49, KBS-57, KBS-81, Shalimar Sarson-1 and Gulchin were selected and crossed in a half diallel mating during rabi 2011-12 at MRCFC, Khudwani, SKUAST-Kashmir. Twenty one F1’s generated along with seven parents were evaluated during rabi 2012-13 for various quantitative traits. Analysis of variance for combining ability revealed highly significant differences for all the traits. Parent KBS-49 was identified as best combiner for yield and yield contributing traits on the basis of significant gca effects. KBS-49 x KBS- 57, KBS-49 x KBS- 81 and KBS-49 x Gulchin were the best cross combinations for yield and other traits. Based on the results obtained in the present study, it is advocated that the parents and crosses identified should be exploited through heterosis breeding and should be used in recombination programme for tapping desirable trangressive segregants in segregating generations. The inter-mating between selected segregants in advanced generations would help to accumulate favorable alleles for further improvement in seed yield and its component traits in Brown Sarson.